Dvigatel'nye umeniya i navyki - Ilyin, E. P. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
Among many scientific problems developed by A.Ts. Puni, the special place is occupied with the problem of motor skills. Discussing with many scientists (in particular, with E.I. Boyko) at the end of 50th the question on sensibleness and unsensibleness of the skill, A.Ts. Puni was against understanding of a skill as an automatism. "On various phases of skill formation (in the process of its automation) the learnt action does not turn in unconscious, but is differently realized. Thus, despite of presence of the not realized movements in the learnt actions (skills) they do not cease to be conscious" he wrote. The automation of actions is not the obligatory attribute of skill. The main in a skill is a workmanship of an action.